2019
DOI: 10.3390/su11123337
|View full text |Cite
|
Sign up to set email alerts
|

Food Systems Sustainability: An Examination of Different Viewpoints on Food System Change

Abstract: Global food insecurity levels remain stubbornly high. One of the surest ways to grasp the scale and consequence of global inequality is through a food systems lens. In a predominantly urban world, urban food systems present a useful lens to engage a wide variety of urban (and global) challenges—so called ‘wicked problems.’ This paper describes a collaborative research project between four urban food system research units, two European and two African. The project purpose was to seek out solutions to what lay b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Food availability at the global, national, or sub-national level does not guarantee food and nutrition security at the community or households level [46,47]. Access to food (physical and economic access) by households or individuals plays a vital role for the food choice of people [48], which is also reflected by the results of this study.…”
Section: Discussionmentioning
confidence: 92%
“…Food availability at the global, national, or sub-national level does not guarantee food and nutrition security at the community or households level [46,47]. Access to food (physical and economic access) by households or individuals plays a vital role for the food choice of people [48], which is also reflected by the results of this study.…”
Section: Discussionmentioning
confidence: 92%
“…The study highlighted a series of cross-cutting issues and pointed a need for a renovated focus on the different nodal points of the food system. Different viewpoints on food system change were examined by Haysom et al (2019). It was also noted that it is possible to recover part of the food during the loading, transportation and unloading stages (Lipińska et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To capture the key lessons learned in FHSD, an integrated perspective on food system research was suggested for developing the learning framework, seeking to integrate dimensions like context, values, disciplinary orientation, and institutional priorities, intersect when researching food systems (Haysom et al, 2019). In addition, the objective of the learning exercise being driven by a feed forward perspective seeking to inform future food system based research, the learning framework included notions of single loop, double loop and triple loop learning.…”
Section: Theoretical Grounding Of Capturing Learningsmentioning
confidence: 99%